Electrochemical performance of α-MnO2 nanorods/activated carbon hybrid supercapacitor - Aravindan, Vanchiappan (2013)
Hollondite type α-MnO2 nanorods are prepared by hydrothermal route at 160 C for 8 h. The structural and morphological properties are examined by X-ray diffraction, BET surface area, scanning electron microscopy and high resolution transmission electron microscopy. Half-cells (Li/α-MnO2) are fabricated to study the Li-cycling behavior in both galvanostaic and potentiostatic modes. The α-MnO2 delivers a stable reversible capacity of ∼80 mA h g–1 at constant current 50 mA g–1 up to 50 cycles when cycled between 1.5–3.8 V versus Li. The hybrid electrochemical capacitor is fabricated using α-MnO2 nanorods (as anode) and activated carbon (as cathode) in non-aqueous medium and cycled between 0–3 V. The hybrid electrochemical capacitor exhibited a stable specific discharge capacitance of 28 F g–1 at high current (60 mA g–1). Further, hybrid electrochemical capacitor displayed a maximum energy and power densities of 9 W h kg–1 and 87 W kg–1, respectively.